A reliability-based probabilistic evaluation of the wave-induced scour depth around marine structure piles. (15th January 2020) - Homaei, Farshad; Najafzadeh, Mohammad
Abstract: In this study, a probabilistic framework was employed to evaluate the relationship among the wave parameters, seabed sediment conditions, and pile groups geometry and the wave-induced-scour depth around pile installed in the marine environment, considering uncertainties due to randomness in some parameters. First, the parameters from the database were categorized into random and deterministic parameters. For describing the random parameters, the probabilistic distribution of them was determined. Then, a probabilistic model was developed using an artificial intelligence method so as to predict the scour depth at pile groups under regular waves. In the second part, this model was employed in the probabilistic framework through 6250000 Monte Carlo sampling analysis to assess the effect of various parameters on the confidence level (reliability) for the scour depth to be less than a specific value. It is concluded that marine structures have to be assessed for scouring under the loading of waves with short periods. Moreover, it is recommended that the pile spacing limited less than 4 times their diameter. A higher number of piles should be considered in parallel to the flow rather than normal to the flow. Highlights: The reliability of scouring depth around marine structure piles was assessed through Monte-Carlo sampling. The proposed limit state function is suitable for the gradient-based reliability methods like FORM and SORM. Values of G / D greater than four have a considerable effect on the reliability of scour depth. For design purposes, a higher number of piles should be provided in parallel to the flow rather than normal to the flow. The K - S test indicated the dominance of the exponential and lognormal distributions on the understudy parameters.